Study of Shearing Temperature on Characterization and Quality of Sheared Edge of SUS304 Austenitic Steel - Pornputsiri, Natthasak; Leetrakul, Pongsakorn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This research aims to investigate the characteristics and quality of the cutting edge of SUS304 stainless steel sheet with 1 mm thickness by hot shearing process. The shearing test was carried out with a circular blanking die with a diameter of 20 mm and the cutting clearance set at 8 percent of the sheet metal thickness. On the pre- blanking, the sheet metal was heated in an electric furnace at 4 temperature levels, consisting of room temperature, 200, 400, and 600 °C. The verification of the characteristics and cutting edge quality of finished blank was determined by region height values on the cutting edge using an optical macroscope, optical microscope and scanning electron microscope. A Vickers hardness tester was used to investigate the micro-hardness of the specimen cutting edge to assess the strain hardening after shearing. The results showed that sheet metal sheared at room temperature had the highest fracture region on the cutting edge and a tendency to deteriorate when the sheet metal temperature increased. At the same time, roll over regions, shear surface regions and burrs tended to increase with an increase in the shearing temperature which was in relation to the hardness test results at the cutting edge. This is because the strain hardening index decreases with increasing temperature. Based on the findings, this experimental data can be applied to determine the optimum shearing temperature conditions for stainless steel sheet metal blanking which is determined by the relationship between the sheet metal temperature which directly affects the finished cutting edge quality.